Lactic acid bacteria from traditionally fermented African food affect the diarrhoeagenic potential of enteroaggregative Escherichia coli - Buys, E.M. (Elna Maria) (University of Pretoria, 2023)
Thesis (PhD (Food Science))--University of Pretoria, 2022.